Uncovering homonymous visual field defects in candidates for pediatric epilepsy surgery. (March 2020) - Neumayr, Lisa; Pieper, Tom; Kudernatsch, Manfred; Trauzettel-Klosinski, Susanne; Staudt, Martin
Abstract: Objectives: Perimetry in children can be challenging due to low cooperation and short attention span. Especially during the pre-surgical work-up of children with pharmaco-refractory epilepsies, however, diagnosing homonymous visual field defects (HVFDs) can be crucial for planning surgical strategies. Here, we evaluated "campimetry" for visual field testing in children. Furthermore, we analyzed strabismus and anomalous head posture as clinical signs for HVFDs. Methods: Campimetry and a standard orthoptic examination were performed in 18 patients (age range: 3 y 2 m–18 y) who underwent epilepsy surgeries in our center during the study period, and in 11 additional patients (age range: 2 y 10 m–22 y 10 m) with suspected or confirmed HVFDs. Results: In 16/18 patients of our unselected surgery cohort, pre- and postoperative campimetry was successfully completed. Of these, only 7/16 patients had intact visual fields pre- and postoperatively, while 5/16 patients already showed preoperative HVFDs and 4/16 patients suffered newly acquired HVFDs as calculated consequences of the surgery. Regarding clinical signs, strabismus (mostly esotropia) and anomalous head posture were specific indicators of HVFDs (strabismus: 6/12 with HVFDs vs 1/18 without; anomalous head posture: 8/12 with HVFDs vs 0/18 without). Conclusions: For perimetry in children with limited cooperation, we suggest campimetry as it allows early detection and fast delineation of HVFDs. This is particularly important in pediatric epilepsy surgery patients, who display a surprisingly high proportion of HVFDs (9/16). Both, strabismus and anomalous head posture can indicate such HVFDs. Therefore, clinicians should pay attention to these clinical signs, especially in the context of epilepsy surgery. Graphical abstract: Image 1 Highlights: Campimetry allows detection and delineation of visual field defects in children. Homonymous visual field defects are frequent in pediatric epilepsy surgery patients. Strabismus and anomalous head posture can indicate homonymous visual field defects.